Gene Mutation and Its Association with Clinicopathological Features in Young Patients with Non-Small-Cell Lung Cancer - Wencui Kong; Zongyang Yu; Wenwu Wang; Jingrong Yang; Jingfang Wang; Zhongquan Zhao (Emergency Medicine International)
Background. We investigated the correlation between genetic mutations and clinical-pathological features in young patients with NSCLC. Methods. Clinicopathologic information of 102 young NSCLC patients was collected. Direct ctDNA sequencing of a portion of these patients was performed. The correlation between EGFR mutation and ALK fusions with clinicopathologic parameters was analyzed. Results. In young NSCLC patients, adenocarcinoma is the major histology (86.9%), and the misdiagnosis rate was as high as 45.7%. EGFR gene mutation was found in 13 patients (31.7%) and common mutations were with EGFR19del mutation (7 cases, 17.1%) and EGFR21L858R mutation (4 patients, 9.7%). EGFR mutation was constantly found in adenocarcinoma and male gender, and ever smokers (100%, P<0.05). Furthermore, ALK fusions were found in 7 patients (31.8%), which include EML-4-ALK fusions; there was a trend that ALK fusions were associated with adenocarcinoma and female gender. However, there was no significant difference in overall survival between patients with or without gene mutations. Conclusions. EGFR mutation and ALK fusions are related to histology, gender, and smoke exposure in young NSCLC patients, and may be effective predictive factors.